Holistic Management of a 9 Year Old Boy Patient with Pulmonary TB Through a Family Doctor Approach in the Rajabasa Indah Community Health Center Area - Fadhila, Syifa Rahmi; Khairunissa Athira Nauli Siregar; Tuti Malindasari; Fitria Saftarina; Belinda Apriannanti Beauty (CV. Jasa Sukses Abadi, 2024)
TB is a disease that is still difficult to complete. The estimated of the number of TB cases in children reaches 99,000 cases or 12% of the total case. The analysis of this study is case report. Assessment is carried out based on a holistic diagnosis from the start, process, and end of the study quantitatively and qualitatively. An. L, 9 years old, has a main complaint of coughing up phlegm. The patient also experienced complaints of not gaining weight, looking thin, and the patient's mother said her child had become less active since she was sick. The patient is a TB patient who has been undergoing OAT treatment for almost 4 months. Some of the factors that can influence the patient's condition are internal and external risk factors. In this case, a diagnosis of tuberculosis was carried out in accordance with current theories and research. After the intervention, there was a decrease in clinical symptoms and changes in the behavior of the patient and his family. The management given is in accordance with the guidelines, it can be seen that changes in behavior and knowledge of the patient and the patient's family are seen after intervention based on evidence-based medicine which is patient-centered, family approach.